Role of Herbal Active Compound in Cardiac Failure Treatment - Upadhyay, Jyotsna; Sonaji, Amle Vandana; Trimbak, Khonde Shital; Ganesh, Chapke Seema; Pawar, Kisan Vivek; Anamika; Kumar, Roshan (Journal for Research in Applied Sciences and Biotechnology, 2024)
The prevalence of cardiovascular diseases (CVDs) is constantly rising, making them a major health burden. In terms of global mortality and morbidity, they are still at the top. An alternate method of treating many illnesses, including CVDs, is the use of medicinal herbs. There is a current, unprecedented push to include herbal remedies into contemporary healthcare systems. The widespread conviction in their safety and the fact that they offer more effective treatment at a lower cost than conventional modern medicines are two of the main factors propelling this movement. However, there has not been enough testing of the purported safety of herbal remedies. As a result, people need to know that medical herbs can be toxic, have possibly fatal side effects, and can interact negatively with other drugs. Experimental evidence suggests that medicinal herbs may be useful in the treatment of cardiovascular diseases (CVDs) due to their ability to inhibit multiple risk factors for these conditions. So, in order to successfully use herbs in CVD therapy, there have been numerous initiatives to transition medicinal herb research from the lab to the clinic. Presented below are cardiovascular diseases (CVDs) and the variables that put people at risk for developing them. Next, we provide a synopsis of herbal medicine's role in the treatment of disease, with a focus on cardiovascular diseases. In addition, information is compiled and examined about the ethnopharmacological therapeutic possibilities and medicinal qualities against cardiovascular diseases of four commonly used plants: ginseng, gingko biloba, ganoderma lucidum, and gymnostemma pentaphyllum. The use of these four plants in the treatment of cardiovascular diseases (CVDs) including myocardial infarction, hypertension, peripheral vascular disorders, coronary heart disease, cardiomyopathies, and dyslipidemias has been well examined. We are also making an effort to describe the current in vitro and in vivo investigations that have attempted to examine the cellular and molecular underpinnings of the four plants' cardio-protective effects. Lastly, we highlighted the effectiveness, safety, and toxicity of these four medicinal herbs by reviewing and reporting the results of current clinical trials. GRAPHICAL ABSTRACT